Voracity of coccinellid species on different phenological stages of the olive pest Saissetia oleae (Homoptera, Coccidae) - Santos, Sónia A.P. (2009)
Coccinellidae are well known predators in agroecosystems. In olive groves they may exert control against scales, such as the black scale, Saissetia oleae (Olivier, 1791). Laboratory studies on the consumption of three phenological stages (eggs, first and second instar nymphs) of S. oleae by four coccinellid species (Chilocorus bipustulatus, Scymnus (Pullus) subvillosus, Scymnus (Mimopullus) mediterraneus and Scymnus (Scymnus) interruptus) were carried out. C. bipustulatus presented a significantly high consumption of eggs, first and second instar nymphs compared with the other species. All coccinellids consumed eggs and first instar nymphs; however the second instar nymphs were only consumed by S. interruptus and C. bipustulatus. In a second experiment, larval stages of C. bipustulatus were reared on different phenological stages of S. oleae. Coccinellid larvae fed with eggs or first instar nymphs completed their life cycle, contrarily to those that were fed with second instar nymphs. The apparent voracity of C. bipustulatus on the different phenological stages of S. oleae is an aspect that suggests the possible use of this coccinellid species in biological control programs against this pest in olive groves.